El síndrome de la alcachofa o de los periodistas sentados. El espejo como medio informativo - Sorela Cajiao, Pedro (Estudios sobre el Mensaje Periodístico, 2002)
Using as his starting point the common tendency of Spanish television channels to just package information or entertainment in a passive way, without actually looking for it -they present basic reality and even do away with interpretation- the author examines the causes of this trend and looks for similarities in other news media (newspapers, radio and news agencies), in what he calls the mirror culture. This tendency is just a symptom of deeper currents of cultural self-absorption that impoverish language, exclude abstraction, imagination and the revolutionary capacity of language, and influence perceptions about freedom itself.
Keywords: Television; newspapers; information; entertainment; realism; interpretation; abstraction; imagination; freedom